(untitled) (Ciudades, 2017)
This article focuses on a particular solution of low price housing –the carré mulhousien–. This was the ideal model built in Oporto and its analysis allows the display of wide frame indications, which will be referenced later in the first practices of social housing of modern architecture in urban context. The paper explores some key themes for the understanding, between different geographies, of working-class housing reform in the end of the 19th Century, putting the emphasis on the single-family detached house and the garden-city ideal.